The name game for contributions: Influence of labeling and earmarking on the perceived tax burden - Jochen Hundsdoerfer; Christian Sielaff; Kay Blaufus; Dirk Kiesewetter; Joachim Weimann (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
In this paper we apply conjoint analysis as an empirical method to study the influence of tax labeling and tax earmarking on the perceived tax burden. As reference for the individual behavior we use the model of a rational utility maximizer described by the economic theory. We determine a significant influence of the labeling and the earmarking of taxes. We can show that the labeling and earmarking effect can decrease the perceived tax burden for the test persons which results in a deviation from a (rational) consumption maximizing behavior. These results give important implications for tax policy regarding further reforms of the tax and contribution system.
Keywords: D03; H20; H51; H52; K34; 330; Tax Labeling; Tax Earmarking; Perceived Tax Burden; Behavioral Taxation; Non Rational Behavior; Conjoint Analysis; Education Allowance; Contribution System; Health Insurance; Steuerpolitik; Zweckgebundene Steuer; Steuermoral; Steuerbelastung; Wahrnehmung; Beschränkte Rationalität; Theorie; Test; Deutschland